1976
DOI: 10.1073/pnas.73.12.4257
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical studies of the conformational properties of ribavirin.

Abstract: One of the factors required for the antiviral activity of the synthetic nucleoside, ribavirin (1-#->-ribofuranosyl-1,2,4-triazole-3-carboxamide), is the ability of the molecule to adopt the substrate conformation specified by the enzyme for which it is a competitive inhibitor, inosine 5'-phosphate dehydrogenase (IMP:NAD+ oxidoreductase, EC 1.2.1.14). The calculated glycosidic minimum for ribavirin is the high syn conformation, which is in agreement with experimental determinations of the molecule's solution co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

1977
1977
2009
2009

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…This comparison indicated that 3-NPN and ribavirin are practically identical in overall structure in the solid state, while differing substantially in hydrogen bonding ability. Interestingly, solution phase studies with ribavirin have revealed a preference for the syn conformation of the heterocyclic base ( , ). On the basis of the substantial structural similarities, the observed differences in biological activity are presumably not a result of conformational effects.…”
Section: Discussionmentioning
confidence: 99%
“…This comparison indicated that 3-NPN and ribavirin are practically identical in overall structure in the solid state, while differing substantially in hydrogen bonding ability. Interestingly, solution phase studies with ribavirin have revealed a preference for the syn conformation of the heterocyclic base ( , ). On the basis of the substantial structural similarities, the observed differences in biological activity are presumably not a result of conformational effects.…”
Section: Discussionmentioning
confidence: 99%
“…8) with those obtained for purine nucleosides (see refs. 8,19,20). Overall, the benzimidazole nucleosides show narrower and deeper depressions in the syn and anti regions than is generally found for the purine nucleosides.…”
mentioning
confidence: 90%
“…The iterative extended Huckel theory used recently in our studies of nucleoside conformation (8,19,20) gives the conformational profiles exhibited in Fig. 4.…”
mentioning
confidence: 99%
“…Calculations that we have done with other crystal forms of adenosine indicate that the conformational energy profile obtained by theoretical calculations on a rigid molecule are modified by the starting coordinates or crystal structure chosen for the calculation. A dramatic example of this has been illustrated by calculations on the two crystal forms of ribavirin (47,48). In general, the high anti conformation in adenosine can be considered as being slightly higher in energy than the anti conformation for most of the probable arrangements of atomic coordinates.…”
mentioning
confidence: 99%